PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERITA FLIPBOOK BERBASIS DIGITAL PADA MATERI PECAHAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA KELAS IV SD - Laura Carla Aritonang; Dini Ramadhani; Bunga Mulyhati (STKIP Subang, 2026)
Based on the results of observations conducted by researchers in class IV of SD Negeri 8 Langsa, it was found that when learning media was not fully used, learning more often used textbooks and picture media. This study aims to develop a learning media product based on digital flipbook storybooks in Mathematics Learning, especially Fraction material for class IV of elementary school. This research is a type of R&D research and development with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluationi